Pengaruh Kemudahan Penggunaan Aplikasi, Nilai Manfaat, dan Desain Antarmuka terhadap Loyalitas Pengguna Shopee - Ramadan, Dinto Putra; Cahyono, Tomy Dwi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the influence of Perceived Ease of Use, Perceived Usefulness, and User Interface Design on User Loyalty toward Shopee in Kabupaten Sumbawa, Indonesia. The research is motivated by the rapid growth of the e-commerce sector in Indonesia, which reached a transaction value of IDR 522 trillion in 2023 and an internet penetration rate of 79.5%. In such a highly competitive environment, user loyalty has become a strategic factor for sustaining e-commerce platforms, including Shopee. This study employed a quantitative approach using a survey method with a descriptive-verificative design. The population consisted of Shopee users in Kabupaten Sumbawa, and 100 respondents were selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS 4 application. The outer model assessment confirmed that all constructs met the criteria for validity and reliability (AVE > 0.5; Composite Reliability > 0.7; Cronbach’s Alpha > 0.7; HTMT < 0.85). The inner model analysis revealed that Perceived Ease of Use (β = 0.315; p < 0.05), Perceived Usefulness (β = 0.428; p < 0.05), and User Interface Design (β = 0.281; p < 0.05) had positive and significant effects on User Loyalty, with Perceived Usefulness being the strongest predictor. These findings highlight that the combination of ease of use, high perceived value, and engaging interface design serves as a crucial determinant of Shopee user loyalty in semi-urban contexts.